Homology-independent multiallelic disruption via CRISPR/Cas9-based knock-in yields distinct functional outcomes in human cells - Zhang, Chenzi (BMC Biol, 2018)
BACKGROUND: Cultured human cells are pivotal models to study human gene functions, but introducing complete loss of function in diploid or aneuploid cells has been a challenge. The recently developed CRISPR/Cas9-mediated homology-independent knock-in approach permits targeted insertion of large DNA at high efficiency, providing a tool for insertional disruption of a selected gene. Pioneer studies have showed promising results, but the current methodology is still suboptimal and functional outcomes have not been well examined. Taking advantage of the promoterless fluorescence reporter systems established in our previous study, here, we further investigated potentials of this new insertional gene disruption approach and examined its functional outcomes. RESULTS: Exemplified by using hyperploid LO2 cells, we demonstrated that simultaneous knock-in of dual fluorescence reporters through CRISPR/Cas9-induced homology-independent DNA repair permitted one-step generation of cells carrying complete disruption of target genes at multiple alleles. Through knocking-in at coding exons, we generated stable single-cell clones carrying complete disruption of ULK1 gene at all four alleles, lacking intact FAT10 in all three alleles, or devoid of intact CtIP at both alleles. We have confirmed the depletion of ULK1 and FAT10 transcripts as well as corresponding proteins in the obtained cell clones. Moreover, consistent with previous reports, we observed impaired mitophagy in ULK1−/− cells and attenuated cytokine-induced cell death in FAT10−/− clones. However, our analysis showed that single-cell clones carrying complete disruption of CtIP gene at both alleles preserved in-frame aberrant CtIP transcripts and produced proteins. Strikingly, the CtIP-disrupted clones raised through another two distinct targeting strategies also produced varied but in-frame aberrant CtIP transcripts. Sequencing analysis suggested that diverse DNA processing and alternative RNA splicing were involved in generating these in-frame aberrant CtIP transcripts, and some infrequent events were biasedly enriched among the CtIP-disrupted cell clones. CONCLUSION: Multiallelic gene disruption could be readily introduced through CRISPR/Cas9-induced homology-independent knock-in of dual fluorescence reporters followed by direct tracing and cell isolation. Robust cellular mechanisms exist to spare essential genes from loss-of-function modifications, by generating partially functional transcripts through diverse DNA and RNA processing mechanisms. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12915-018-0616-2) contains supplementary material, which is available to authorized users.